Effectiveness in Dynamic Balance: a Comparison between Foot Muscle Strengthening Using Elastic Band and without Elastic Band in Children Aged 8–12 with Flexible Flatfeet - Listyorini, Indri; Shanti, Marietta; Prabowo, Tertianto (International Journal of Integrated Health Sciences, 2015)
Objective: To compare the effects of foot muscle strengthening exercises with and without elastic band to the dynamic balance function in children aged 8–12 years with flexible flatfeet.Methods: Forty-one children (aged 8–12 years) with flexible flatfeet and dynamic balance problem were randomly allocated into either the intervention or control group. Both groups received thrice weekly training for 6 weeks. The foot strengthening exercise regimens consisted of pronation, supination, short foot, and tiptoeing using elastic band for the intervention group and without elastic band for the control group. Star Excursion Balance Test (SEBT) was tested before and after 6 weeks of training. Results: A statistically significant difference of normalized SEBT scores was found for both groups in both legs (p=0.00, p<0.05). The intervention group was significantly better than the control group for both right and left legs (p=0.00, p<0.05). Conclusions: Foot muscle strengthening either with or without elastic band improves dynamic balance in children aged 8–12 years with flexible flatfeet. Exercise given with elastic band significantly shows better improvement in the dynamic balance compared to without elastic band.Keywords: Flexible flatfeet, strengthening exercises, elastic band, dynamic balance, star excursion balance test DOI: 10.15850/ijihs.v3n1.404